READING PARK FORUM: ROLE AND IMPACT ON OPTIMIZING READING PARK COMMUNITY - Elpa Hermawan; Danang Dwi Harmoko (Citra Dharma Cindekia, 2022)
As one of the pillars of strengthening literacy in society, reading gardens are not only given support but also reinforcement. Reading gardens must be positioned in the chain of government policies related to the community literacy movement. This study aims to explore the potential roles and impacts of reading garden forums for optimizing community reading gardens. This study uses a descriptive qualitative approach. Data were obtained using the Systematic Literature Review (SLR) method. Various articles and other reference sources were obtained from Scopus, ScienceDirect Google Scholar, and DOAJ. From the search results, 282 articles were obtained which were then taken by some of the most relevant studies. Field observations and interviews were conducted to strengthen the data. This research resulted in findings of the role and impact of FTBM. The role of the forum includes overcoming the problem of shortage of reading resources through donation programs and book exchanges; a forum for exchanging experiences, sharing ideas, and ideas about managing reading gardens; and a place to advocate. Then, the impact of FTBM is the impact of resource circulation, the impact of empowerment, and the impact of advocacy for community reading garden activists